IMPLEMENTASI SISTEM INFORMASI GEOGRAFIS UNTUK PENYUSUNAN DATABASE UMKM DI KECAMATAN MANDIRAJA KABUPATEN BANJARNEGARA - Fanny Tri Raditya (Unit Penelitian dan Pengabdian Masyarakat (UP2M) Politeknik Banjarnegara, 2021)
Micro, Small and Medium Enterprises are a form of productive economic business carried out by individuals or individual business entities that meet the criteria for Micro, Small and Medium Enterprises (MSMEs). MSMEs have an important role in the regional local economy (Sriya, 2010). This is indicated by the ability of MSMEs to drive regional economic activities and provide employment opportunities. The existence of MSMEs in Mandiraja District has not been followed by good data management. With so much information, the Mandiraja district office has not yet fully provided complete information, many people do not know the location of the existence of MSMEs causing a lack of improvement in surrounding businesses. So it is necessary to organize data that is integrated with Geographic Information Systems in order to make it easier to read information related to MSMEs in Mandiraja District, Banjarnegara Regency. The purpose of this research is to build a Geographic Information System for Agro-industry MSMEs in Mandiraja District, Banjarnegara Regency. Keywords: micro, small and medium enterprises, geographic information systems